أدب الرِّحل في الأندلس والمغرب بين التأريخ والتخييل - حورية, بن يطو (جامعة الوادي - University of Eloued, 2023)
صرف الرحالة الأندبسيون والمغاربة جهدهم العلمي والعملي بأعلى درجات الدّقة والكفاءة نحو التعامل مع التراث الحضاري العربي الذي امتدت سيادته على دنيا المشارق والمغارب من آدابه وقيّمه وعاداته وتقاليده وثقافته الشعبية، لجعل مدونتهم الرّحلية موسوعة تتقاطع على متنها العديد من الأنساق: اللغوية التاريخية، الجغرافية العلمية والأدبية، يتفاعل فيها الواقعي بالتخييلي، لإثارة صورة بصرية في ذهن المتلقي وجعله أكثر قابلية على الإنفعال وهذا الطرح يجعل النص الرّحلي يقوم على فكرة رئيسة مدارها سيكولوجي حسّي، ذلك أن الرّحالة حين يكتب لا يكتب لمجرد التأريخ لرحلة الكشف والبحث، بل ليشخص ما يحتوي عليه باطنه من مشاعر وعواطف، وليست لهذه المشاعر والعواطف أية قيمة فنية ما لم يهتز لها القارئ ويتجاوب مع صاحبها تجاوبا كاملا. Abstract : The Andalusian and Moroccan travelers expended their scientific and practical efforts with the highest degree of accuracy and efficiency in dealing with the Arab cultural heritage whose sovereignty extended to the Oriental and Maghreb worlds from its literaturevalues customs, traditions and popular culture, to make their Travelog blog an encyclopedia on which many people intersect: Historical linguistic, geographical, scientific, and literary, in which realism interacts with imaginary, to stimulate a visual image in the recipient's mind and make it more emotive. This subtraction makes the phased text based on the idea of the head of its psychological orbit sensual, as travelers, when they write, do not write just for the sake of the history of the journey of discovery and research, but for the sake of a person, the sentiments and emotions inside of it. These feelings and emotions have no artistic value unless the reader is shaken and the person responds fully.
مقال
Keywords: الرّحلة؛ أدب الرّحلة؛ التخييل؛ التأريخ؛ المتلقي؛ الحس؛ المشاهدة.